Beyond The Needle: Biotech’s Delivery Challenge - FELCONE, LINDA HULL (BioCommunications LLC, 2004)
Finding new ways to administer biologics could lead to higher patient acceptance and lower costs, and prove crucial as biotech companies release products aimed at more prevalent diseases. Here’s a look at the emerging world of noninjectable biologics.